Effects of Variation Straps Length Towards the Reduction of Liquid Sloshing in a Downscaled Flexitank - William, Jason (Progress in Engineering Application and Technology, 2023)
This thesis presents a study on the effects of variation strap length on reducing liquid sloshing in downscaled flexitanks. The research aimed to investigate the optimal strap length that can minimize the sloshing force and protect the shipping container during transportation. The experimental approach used Force Sensing Resistors (FSRs) to measure the sloshing force while varying the speed of a transportation simulation tester. The experiments were conducted in accordance with ASTM D999-2015 Standard Test Methods for Vibration Testing of Shipping Containers. The data collected were used to plot the graphs of force against the strap length reduction under different speeds. The graphs were plotted to determine the effectiveness of the strap length reduction and also to identify which part of the downscaled flexitank produced the most force. The results of this study could provide valuable insights into the design and operation of flexitanks to improve the safety and efficiency of liquid transportation, especially in the food and beverage industry and other fields that rely on flexitanks as a means of liquid transportation